Computational Radiology for Orthopaedic Interventions - Zheng, Guoyan; Li, Shuo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a cohesive overview of the current technological advances in computational radiology, and their applications in orthopaedic interventions. Contributed by the leading researchers in the field, this volume covers not only basic computational radiology techniques such as statistical shape modeling, CT/MRI segmentation, augmented reality and micro-CT image processing, but also the applications of these techniques to various orthopaedic interventional tasks. Details about following important state-of-the-art development are featured: 3D preoperative planning and patient-specific instrumentation for surgical treatment of long-bone deformities, computer assisted diagnosis and planning of periacetabular osteotomy and femoroacetabular impingement, 2D-3D reconstruction-based planning of total hip arthroplasty, image fusion for  computer-assisted bone tumor surgery, intra-operative three-dimensional imaging in fracture treatment, augmented reality based orthopaedic interventions and education, medical robotics for musculoskeletal surgery, inertial sensor-based cost-effective surgical navigation, and computer assisted hip resurfacing using patient-specific instrument guides. Edited and authored by leading researchers in the field, this work is an essential reference for biomedical engineers, computer scientists and orthopaedic surgeons to develop or use computational radiology approaches for orthopaedic surgery and interventions.
Preface -- Statistical Shape Modeling of Musculoskeletal Structures and Its Applications, by Hans Lamecker, Stefan Zachow -- Automated 3D Lumbar Intervertebral Disc Segmentation from MRI Data Sets, by Xiao Dong and Guoyan Zheng -- Registration for Orthopaedic Interventions, by Ziv Yaniv -- 3D Augmented Reality Based Orthopaedic Interventions, by Xinran Zhang, Zhencheng Fan, Junchen Wang  and Hongen Liao -- Fully Automatic Segmentation of Hip CT Images, by Chengwen Chu, Junjie Bai, Xiaodong Wu, and Guoyan Zheng -- Quantification of Implant Osseointegration by means of a Reconstruction Algorithm on Micro-computed Tomography Images, by R. Bieck, C. Zietz, C. Gabler, R. Bader -- Surgical Treatment of Long-bone Deformities: 3D Preoperative Planning and Patient-specific Instrumentation, by Philipp Fürnstahl, Andreas Schweizer, Matthias Graf, Lazaros Vlachopoulos, Sandro Fucentese, Stephan Wirth, Ladislav Nagy, Gabor Szekely, Orcun Goksel -- Preoperative Planning of Periacetabular Osteotomy (PAO) by Timo M. Ecker, Li Liu, Guoyan Zheng, Christoph E. Albers, Klaus A. Siebenrock -- Computer Assisted Diagnosis and Treatment Planning of Femoroacetabular Impingement (FAI),by Christoph E. Albers, Markus S. Hanke, Timo M. Ecker, Pascal C. Haefeli, Klaus A. Siebenrock, Simon D. Steppacher, Corinne A. Zurmühle, Joseph M. Schwab and Moritz Tannast -- 2D-3D Reconstruction-based Planning of Total Hip Arthroplasty, by Guoyan Zheng, Steffen Schumann, Steven Balestra, Benedikt Thelen, Lutz-P. Nolte -- Image Fusion for Computer-assisted Bone Tumor Surgery, by Kwok Chuen Wong -- Intraoperative Three-Dimensional Imaging in Fracture Treatment with a Mobile C-Arm, by Jochen Franke, Nils Beisemann -- Augmented Reality in Orthopaedic Interventions and Education, by Pascal Fallavollita, Lejing Wang, Simon Weidert, Nassir Navab -- State of the art of ultrasound based registration in computer assisted orthopedic interventions, by Steffen Schumann -- Medical Robotics for Musculoskeletal Surgery, by Sanghyun Joung, Ilhyung Park -- A Cost‐effective Surgical Navigation Solution for Periacetabular Osteotomy (PAO) Surgery, by Silvio Pflugi, Li Liu, Timo M. Ecker, Jennifer Cullmann-Bastian, Klaus Siebenrock, Guoyan Zheng -- Computer Assisted Hip Resurfacing Using Patient-Specific Instrument Guides, by Manuela Kunz, John F Rudan.
Keywords: Biomedical engineering; Radiology; Signal processing; Mathematics; Medical physics; Biomedical Engineering and Bioengineering; Radiology; Signal, Speech and Image Processing; Mathematics; Medical Physics